PROTECTIVE FILM-FORMING FILM, PROTECTIVE FILM-FORMING SHEET, PROTECTIVE FILM-FORMING COMPOSITE SHEET, AND APPARATUS FOR PRODUCING THE SAME
Patent Information
- Application Number
- JP2021049006
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-03-23
Smart Images

Figure 0007635038000005 
Figure 0007635038000006 
Figure 0007635038000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a protective film-forming film, a sheet for forming a protective film, a composite sheet for forming a protective film, and a method for manufacturing a device. In particular, the present invention relates to a protective film-forming film that is suitably used for protecting a workpiece such as a semiconductor wafer or a processed product such as a semiconductor chip obtained by processing the workpiece, a sheet for forming a protective film and a composite sheet for forming a protective film that include the protective film-forming film, and a method for manufacturing a device such as a semiconductor chip. [Background technology]
[0002] In recent years, semiconductor devices have been manufactured using a mounting method called flip chip bonding. In this mounting method, when mounting a semiconductor chip having a circuit surface on which convex electrodes such as bumps are formed, the circuit surface side of the semiconductor chip is inverted (face down) and bonded to the chip mounting part. This results in a structure in which the back side of the semiconductor chip on which no circuit is formed is exposed.
[0003] For this reason, a hard protective film made of an organic material is often formed on the back side of the semiconductor chip to protect the semiconductor chip from shocks during transportation, etc. To form such a protective film, an uncured resin film (hereinafter referred to as "protective film-forming film"), which is a precursor of the protective film, is used. The protective film-forming film is attached to the back side of the semiconductor wafer and is diced together with the wafer to separate the chips. By curing the protective film-forming film, a chip having a protective film on the back side (chip with protective film) is obtained.
[0004] In addition, in order to identify the semiconductor chip, marks, letters, etc. are marked on the surface of the protective film-forming film by, for example, laser marking. Patent Document 1 describes that the protective film-forming film has a resin layer α that is adhered to the semiconductor chip and a resin layer β that is printed by a laser, and that the gloss value of the surface of the resin layer β after curing is a predetermined value or more. It describes that this protective film-forming film can improve the recognition of the laser marking while increasing reliability. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2014 / 148496 Summary of the Invention [Problem to be solved by the invention]
[0006] When mounting a chip with a protective film on a substrate by the face-down method, the chip with the protective film and the substrate are electrically and mechanically bonded, for example, by a heating process such as a reflow process. To achieve good bonding, flux is usually applied to at least one of the electrode portions of the chip with the protective film and the electrode portions of the substrate before the heating process.
[0007] The flux contains resin, solvent, activator, viscosity adjuster, etc. During the reflow process, most of the flux evaporates when the electrode part of the protective film-covered chip and the electrode part of the substrate melt and join together. However, after the reflow process, flux residue may be left on the substrate on which the protective film-covered chip is mounted.
[0008] Such flux residues cause poor electrical continuity, corrosion, and poor appearance, so they are usually removed by defluxing. The cleaning agents used for defluxing (deflux agents) contain solvents to remove the flux residues.
[0009] The present inventors have found that if a solvent contained in a cleaning agent used for flux cleaning penetrates into the interface between the protective film and the chip during flux cleaning, peeling between the protective film and the chip becomes evident in a reliability test of the mounting board.
[0010] The present invention has been made in consideration of such findings, and aims to provide a protective film-forming film in which peeling between the protective film and the chip caused by flux cleaning is suppressed, a protective film-forming sheet and a protective film-forming composite sheet including the protective film-forming film, and a method for manufacturing devices such as semiconductor devices. [Means for solving the problem]
[0011] The aspects of the present invention are as follows. [1] A protective film-forming film for forming a protective film, This is a protective film-forming film in which the shear strength of the interface between the protective film and the silicon chip after immersion in 2-aminoethanol is 33 N / 5 mm or more. [2] The protective film-forming film according to [1], wherein the contact angle of 2-aminoethanol on the protective film surface is less than 55°. [3] A protective film-forming film according to [1] or [2], in which the ratio of the gloss value of the protective film surface after immersion in 2-aminoethanol to the gloss value of the protective film surface before immersion in 2-aminoethanol is 40% or more and less than 130%. [4] The protective film-forming film according to any one of [1] to [3], wherein the Young's modulus of the protective film after immersion in 2-aminoethanol is less than 1000 MPa. [5] The protective film-formed film according to any one of [1] to [4], wherein the protective film has a breaking elongation of 15% or more after immersion in 2-aminoethanol. [6] A sheet for forming a protective film comprising the protective film-forming film according to any one of [1] to [5] and a release film arranged on at least one main surface of the protective film-forming film. [7] A composite sheet for forming a protective film, comprising the protective film-forming film according to any one of [1] to [5] and a support sheet for supporting the protective film-forming film. [8] A step of attaching a protective film-forming film of the sheet for forming a protective film described in [6] or a protective film-forming film of the composite sheet for forming a protective film described in [7] to the back surface of a work; A step of converting the attached protective film-forming film into a protective film; A step of obtaining a plurality of workpieces each having a protective film or a protective film-forming film by dividing the workpiece having a protective film or a protective film-forming film on a back surface thereof; placing a workpiece having a protective film or a protective film-forming film on a substrate in contact with the flux; A process of heating a workpiece having a protective film or a protective film-forming film disposed on a substrate and the substrate; and cleaning the substrate on which the workpiece with the protective film is placed with a flux cleaner. [9] A method for manufacturing the device described in [8], comprising a step of performing laser marking on the protective film or the protective film-forming film. Effect of the Invention
[0012] According to the present invention, it is possible to provide a protective film-forming film in which peeling between the protective film and a workpiece such as a chip caused by flux cleaning is suppressed, a protective film-forming sheet and a protective film-forming composite sheet including the protective film-forming film, and a method for manufacturing devices such as semiconductor devices. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic cross-sectional view of an example of a chip having a protective film obtained by forming a protective film from the protective film-forming film according to this embodiment. [Figure 2A] FIG. 2A is a schematic cross-sectional view of an example of the protective film-forming sheet according to this embodiment. [Figure 2B] FIG. 2B is a schematic cross-sectional view of another example of the sheet for forming a protective film according to this embodiment. [Figure 3A] FIG. 3A is a schematic cross-sectional view of an example of the composite sheet for forming a protective film according to this embodiment. [Figure 3B] FIG. 3B is a schematic cross-sectional view of another example of the composite sheet for forming a protective film according to the present embodiment. [Figure 4A] FIG. 4A is a schematic cross-sectional view showing an example of the sheet for forming a protective film according to this embodiment after punching. [Figure 4B] FIG. 4B is a schematic cross-sectional view showing a state after punching another example of the sheet for forming a protective film according to this embodiment. [Figure 5A] FIG. 5A is a schematic cross-sectional view for explaining a step of attaching the protective film forming sheet according to this embodiment to a wafer. [Figure 5B] FIG. 5B is a schematic cross-sectional view for explaining a step of attaching the composite sheet for forming a protective film according to this embodiment to a wafer. [Figure 6] FIG. 6 is a schematic cross-sectional view for explaining a step of dividing the wafer with the protective film into individual pieces. [Figure 7] FIG. 7 is a schematic cross-sectional view for explaining the step of disposing the chip with the protective film on the substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings based on specific embodiments. First, the main terms used in this specification will be explained.
[0015] The work is a plate-like body to which the protective film-forming film according to the present embodiment is attached and processed. Examples of the work include wafers and panels. Specifically, examples of the work include semiconductor wafers and semiconductor panels. Examples of the processed product of the work include chips obtained by dicing a wafer. Specifically, examples of the processed product include semiconductor chips obtained by dicing a semiconductor wafer. In this case, the protective film is formed on the back side of the wafer and the chip.
[0016] The "front surface" of a workpiece such as a wafer refers to the surface on which circuits, convex electrodes such as bumps, etc. are formed, and the "back surface" refers to the surface on which circuits, electrodes (for example, convex electrodes such as bumps), etc. are not formed.
[0017] Wafer dicing refers to dividing a wafer into individual circuits to obtain chips.
[0018] In this specification, for example, "(meth)acrylate" is used as a term indicating both "acrylate" and "methacrylate," and the same applies to other similar terms.
[0019] The term "energy rays" refers to ultraviolet rays, electron beams, etc., and is preferably ultraviolet rays.
[0020] The release film is a film that supports the protective film-forming film in a peelable manner. The term "film" is not limited to a specific thickness, and is used to include a sheet.
[0021] The mass ratios in the description of compositions such as the composition for protective film-forming films are based on the active ingredient (solid content), and do not include the solvent unless otherwise specified.
[0022] (1. Protective film forming film) The protective film-forming film according to this embodiment is attached to a workpiece to form a protective film for protecting the workpiece or a processed product of the workpiece.
[0023] "Making a protective film" means making the protective film-forming film have sufficient properties to protect the workpiece or a processed product of the workpiece. Specifically, when the protective film-forming film according to the present embodiment is curable, "making a protective film" means making the uncured protective film-forming film into a cured product. In other words, the protective film-forming film that has been made into a protective film is a cured product of the protective film-forming film and is different from the protective film-forming film.
[0024] After the workpiece is superimposed on the curable protective film-forming film, the protective film-forming film is cured, whereby the protective film can be firmly adhered to the workpiece and a durable protective film can be formed.
[0025] On the other hand, when the protective film-forming film according to the present embodiment does not contain a curable component and is used in an uncured state, the protective film-forming film according to the present embodiment becomes a protective film when the protective film-forming film according to the present embodiment is attached to a workpiece. In other words, the protective film-forming film that has become a protective film is the same as the protective film-forming film.
[0026] When high protective performance is not required, the protective film-forming film does not need to be cured, and therefore the protective film-forming film is easy to use.
[0027] In this embodiment, the protective film-forming film is preferably curable. Therefore, the protective film is preferably a cured product. Examples of the cured product include a heat-cured product and an energy ray-cured product. In this embodiment, the protective film is more preferably a heat-cured product.
[0028] In addition, it is preferable that the protective film-forming film has adhesiveness at room temperature (23°C) or exhibits adhesiveness when heated. This allows the workpiece to be laminated to the protective film-forming film when the workpiece is placed on the protective film-forming film. Therefore, positioning can be reliably performed before the protective film-forming film is cured.
[0029] The protective film-forming film may be composed of one layer (single layer) or may be composed of two or more layers. When the protective film-forming film has multiple layers, these multiple layers may be the same or different from each other, and the combination of layers constituting these multiple layers is not particularly limited.
[0030] In this embodiment, the protective film-forming film is preferably one layer (single layer). A one-layer protective film-forming film can be easily produced because it can obtain high precision in terms of thickness. In addition, when the protective film-forming film is composed of multiple layers, it is necessary to consider the adhesion between the layers and the elasticity of each layer, which may cause a risk of peeling from the adherend. When the protective film-forming film is one layer, the above risk can be reduced and the design freedom is increased. In addition, the risk of peeling between layers due to differences in thermal elasticity between layers in processes where temperature changes occur (during reflow processing or when using the device) can also be reduced.
[0031] The thickness of the protective film-forming film is not particularly limited, but is preferably 100 μm or less, 70 μm or less, 45 μm or less, or 30 μm or less. The thickness of the protective film-forming film is preferably 5 μm or more, 10 μm or more, or 15 μm or more. When the thickness of the protective film-forming film is within the above range, the protective performance of the obtained protective film becomes good.
[0032] The thickness of the protective film-forming film means the thickness of the entire protective film-forming film. For example, the thickness of a protective film-forming film composed of multiple layers means the total thickness of all layers constituting the protective film-forming film.
[0033] The following describes the protective film formed on the tip as the processed product of the workpiece. Specifically, the protective film formed by converting the protective film-forming film according to the present embodiment into a protective film will be described using the tip 70 with protective film shown in FIG.
[0034] As shown in Figure 1, in a chip 70 with a protective film, a protective film 1 is formed on the back side (upper side in Figure 1) of a chip 6a, and a convex electrode 6b is formed on the front side (lower side in Figure 1) of the chip 6a.
[0035] A circuit is formed on the front surface of the chip 6a, and the convex electrodes 6b are formed so as to be electrically connected to the circuit. Examples of the convex electrodes 6b include bumps and pillar electrodes.
[0036] In this embodiment, the protective film-equipped chip 70 is placed on the chip-mounting substrate so that the surface on which the convex electrodes 6b are formed faces the chip-mounting substrate. At this time, flux or solder paste for bonding the protective film-equipped chip 70 to the chip-mounting substrate is applied to the positions on the chip-mounting substrate corresponding to the protective film-equipped chip 70 or to the convex electrodes. Thereafter, the convex electrodes 6b and the substrate are electrically and mechanically bonded by a predetermined heating process (for example, a reflow process), and the protective film-equipped chip 70 is mounted on the substrate.
[0037] Flux is used to clean electrodes, remove oxide films from solder, reduce the surface tension of solder, etc. Solder paste also contains flux. Flux includes, for example, resin containing rosin or rosin-modified product, solvent, activator for removing oxide, viscosity adjuster, etc.
[0038] Although most of the flux volatilizes due to heating such as in a reflow process, flux residue may remain at the location where the flux was applied. Also, when applying flux, flux may be applied to an unintended location, resulting in flux residue at that location. Since such flux residue can cause poor adhesion of the underfill, corrosion such as migration, and poor appearance, flux cleaning is performed on boards on which chips with protective film are mounted to remove the flux residue.
[0039] In flux cleaning, the entire substrate on which the chips with protective film are mounted is immersed in the cleaning liquid, or the cleaning liquid is sprayed onto the entire substrate, so that the chips with protective film come into contact with the cleaning liquid.
[0040] When the cleaning agent comes into contact with the chip with the protective film, the components contained in the cleaning agent may penetrate into the interface between the protective film and the chip. As a result, in a reliability test of the substrate after mounting, floating or peeling occurs at the interface between the protective film and the chip, reducing reliability. In this embodiment, in order to suppress floating or peeling at the interface between the protective film and the chip caused by flux cleaning, the physical properties of the protective film are controlled as follows. Note that the physical properties of the protective film shown below are the physical properties after the protective film-forming film is made into a protective film.
[0041] (1.1 Shear strength of the interface between the protective film and the silicon chip after immersion in 2-aminoethanol) Examples of components contained in the cleaning agent used in flux cleaning include alcohol-based cleaning agents, amine-based cleaning agents, etc. In this embodiment, 2-aminoethanol is selected as the component contained in the cleaning agent, and a configuration is shown that can prevent 2-aminoethanol from penetrating into the interface between the protective film and the chip.
[0042] In this embodiment, the shear strength of the interface between the protective film and the silicon chip after immersion in 2-aminoethanol is 33 N / 5 mm or more. Since the shear strength of the interface is within the above range, even if 2-aminoethanol comes into contact with the chip with the protective film, the adhesion of the interface between the protective film and the chip is well maintained, so that the penetration of 2-aminoethanol into the interface between the protective film and the chip can be suppressed. Therefore, the adhesion reliability of the interface of the chip with the protective film can be improved.
[0043] The shear strength of the interface is preferably 35 N / 5 mm or more, more preferably 38 N / 5 mm or more. On the other hand, although there is no particular upper limit to the shear strength of the interface, from the viewpoints of the constituent materials and manufacturing method, it is preferably 60 N / 5 mm or less, more preferably 50 N / 5 mm or less.
[0044] (1.2 Contact angle of 2-aminoethanol on protective film surface) In this embodiment, the contact angle of 2-aminoethanol on the protective film surface is preferably less than 55°. When the contact angle is within the above range, 2-aminoethanol easily spreads on the protective film surface. As a result, 2-aminoethanol that comes into contact with the protective film is easily taken up by the protective film, and the 2-aminoethanol that penetrates into the interface between the protective film and the chip can be suppressed.
[0045] The contact angle of 2-aminoethanol on the protective film surface is more preferably 52° or less, and even more preferably 48° or less. On the other hand, although there is no particular lower limit for the contact angle, it is preferably 30° or more, and more preferably 40° or more.
[0046] The contact angle of 2-aminoethanol may be measured by a known method, the specific method of which will be described in the Examples.
[0047] (1.3 Change in gloss of protective film surface before and after immersion in 2-aminoethanol) In this embodiment, the gloss change rate of the protective film surface before and after immersion in 2-aminoethanol is preferably 40% or more and less than 130%. The gloss change rate is expressed as the ratio of the gloss value of the protective film surface after immersion in 2-aminoethanol to the gloss value of the protective film surface before immersion in 2-aminoethanol.
[0048] When 2-aminoethanol comes into contact with the protective film, the surface condition of the protective film changes. As a result, the gloss value, which indicates the glossiness of the protective film surface, also changes. Incidentally, in order to facilitate identification of chips with a protective film, marking is sometimes performed on the surface of the protective film. An example of such marking is laser marking. By performing laser marking, the surface of the protective film is scraped off, or a convex portion is formed due to an increase in the volume of the protective film.
[0049] That is, since laser marking also changes the surface condition of the protective film, if the surface condition of the protective film changes significantly due to immersion in 2-aminoethanol, the distinguishability of the marking may decrease.
[0050] Therefore, by setting the gloss change rate within the above range, it is possible to suppress changes in the surface condition of the protective film caused by immersion in 2-aminoethanol, and to maintain good distinguishability of the marking.
[0051] The gloss change rate is more preferably 120% or less, while the gloss change rate is more preferably 80% or more, and even more preferably 95% or more.
[0052] The gloss value of the protective film before and after immersion in 2-aminoethanol is measured in accordance with JIS Z 8741. That is, the measurement is performed in the same manner as the measurement method specified in JIS Z 8741, but the measurement conditions may be different. The specific measurement method will be described in the examples.
[0053] (1.4 Young's modulus of protective film after immersion in 2-aminoethanol) In this embodiment, the Young's modulus of the protective film after immersion in 2-aminoethanol is preferably less than 1000 MPa. It is considered that the protective film becomes soft while maintaining adhesion to the chip by having the Young's modulus within the above range. That is, even if 2-aminoethanol comes into contact with the chip with the protective film, it is considered that the protective film takes in 2-aminoethanol before 2-aminoethanol penetrates into the interface between the protective film and the chip, and the protective film becomes soft and altered. Furthermore, by softening the protective film, the stress applied to the interface between the protective film and the chip due to the sudden temperature change can be reduced in a reliability test involving a sudden temperature change, so that lifting or peeling at the interface can be further suppressed.
[0054] The Young's modulus of the protective film after immersion in 2-aminoethanol is more preferably 900 MPa or less, and even more preferably 800 MPa or less. On the other hand, the lower limit of the Young's modulus of the protective film after immersion in 2-aminoethanol is not particularly limited, but is preferably 300 MPa or more, and even more preferably 500 MPa or more, from the viewpoint of exerting the function of the protective film.
[0055] The Young's modulus of the protective film after immersion in 2-aminoethanol is measured in accordance with JIS K 7127. That is, it is measured in the same manner as the measurement method specified in JIS K 7127, but the measurement conditions may be different. The specific measurement method will be described in the examples.
[0056] (1.5 Breaking elongation of protective film after immersion in 2-aminoethanol) In this embodiment, the breaking elongation of the protective film after immersion in 2-aminoethanol is preferably 15% or more. It is considered that the breaking elongation is within the above range, and the protective film becomes soft while maintaining adhesion to the chip, as in the case of Young's modulus. That is, even if 2-aminoethanol comes into contact with the chip with the protective film, it is considered that the protective film takes in 2-aminoethanol before 2-aminoethanol penetrates into the interface between the protective film and the chip, and the protective film becomes soft and altered. Furthermore, by softening the protective film, the stress applied to the interface between the protective film and the chip due to the sudden temperature change can be reduced in a reliability test involving a sudden temperature change, and thus lifting or peeling at the interface can be further suppressed.
[0057] The breaking elongation of the protective film after immersion in 2-aminoethanol is more preferably 17% or more, and even more preferably 19% or more. On the other hand, the upper limit of the breaking elongation of the protective film after immersion in 2-aminoethanol is not particularly limited, but from the viewpoint of exerting the function of the protective film, it is more preferably 40% or less, and even more preferably 30% or less.
[0058] The breaking elongation of the protective film after immersion in 2-aminoethanol may be measured together with the Young's modulus in accordance with JIS K 7127. A specific measurement method will be described in the Examples.
[0059] (1.6 Composition for protective film-forming film) As long as the protective film has the above-mentioned physical properties, the composition of the protective film-forming film is not particularly limited. In this embodiment, the composition constituting the protective film-forming film (composition for protective film-forming film) is preferably a resin composition containing at least a polymer component (A), a curable component (B), a filler (E), and a coupling agent (F). The polymer component is a component that can be considered to be formed by a polymerization reaction of a polymerizable compound. In addition, the curable component is a component that can undergo a curing (polymerization) reaction. In the present invention, the polymerization reaction also includes a polycondensation reaction.
[0060] In addition, the component contained in the polymer component may also be a curable component. In this embodiment, when the composition for forming a protective film contains a component that corresponds to both such a polymer component and a curable component, the composition for forming a protective film is considered to contain both a polymer component and a curable component.
[0061] 1.6.1 Polymer Components The polymer component (A) imparts film-forming properties (film-forming properties) to the protective film-forming film while imparting appropriate tack, thereby ensuring uniform attachment of the protective film-forming film to the workpiece. The weight-average molecular weight of the polymer component is usually in the range of 50,000 to 2,000,000, preferably 100,000 to 1,500,000, and particularly preferably 200,000 to 1,000,000. Examples of such polymer components include acrylic resins, urethane resins, phenoxy resins, silicone resins, and saturated polyester resins, and acrylic resins are particularly preferred.
[0062] In this specification, unless otherwise specified, the "weight average molecular weight" is a polystyrene equivalent value measured by gel permeation chromatography (GPC). Measurements by such a method are performed, for example, using a high-speed GPC device "HLC-8120GPC" manufactured by Tosoh Corporation with a high-speed column "TSK guard column H XL -H", "TSK Gel GMH XL ", "TSK Gel G2000 H XL (All of the above are manufactured by Tosoh Corporation) connected in the above order, the column temperature was 40° C., the liquid flow rate was 1.0 mL / min, and the detector was a differential refractometer.
[0063] Examples of the acrylic resin include (meth)acrylic acid ester copolymers consisting of a (meth)acrylic acid ester monomer and a structural unit derived from a (meth)acrylic acid derivative. The (meth)acrylic acid ester monomer here preferably includes a (meth)acrylic acid alkyl ester having an alkyl group with 1 to 18 carbon atoms, specifically methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, etc. Examples of the (meth)acrylic acid derivative include (meth)acrylic acid, glycidyl (meth)acrylate, hydroxyethyl (meth)acrylate, etc.
[0064] In this embodiment, in order to control the adhesiveness to the workpiece and the adhesive properties, it is preferable to introduce a hydroxyl group into the acrylic resin using hydroxyethyl acrylate or the like.
[0065] The glass transition temperature of the acrylic resin is preferably -70°C to 40°C, -35°C to 35°C, -20°C to 30°C, -10°C to 25°C, or -5°C to 20°C. By setting the lower limit of the glass transition temperature of the acrylic resin to the above value, excessive swelling and deformation caused by the protective film absorbing the flux cleaner is suppressed, and it becomes easier to maintain the shape of the protective film in the same shape as the chip. In addition, by setting the upper limit of the glass transition temperature of the acrylic resin to the above value, the tack of the protective film-forming film is appropriately increased, the adhesive strength of the protective film-forming film to the workpiece is improved, and the adhesive strength of the protective film to the workpiece is appropriately improved.
[0066] When an acrylic resin has m types of structural units (m is an integer of 2 or more), the glass transition temperature of the acrylic resin can be calculated as follows: That is, when m types of monomers that derive the structural units in the acrylic resin are each assigned a unique number from 1 to m in sequence and named "monomer m", the glass transition temperature (Tg) of the acrylic resin can be calculated using the Fox formula shown below.
number
number
[0067] For Tgk, values listed in the Polymer Data Handbook, Adhesive Handbook, Polymer Handbook, etc. can be used. For example, the Tgk of a homopolymer of methyl acrylate is 10°C, the Tgk of a homopolymer of n-butyl acrylate is -54°C, the Tgk of a homopolymer of methyl methacrylate is 105°C, the Tgk of a homopolymer of 2-hydroxyethyl acrylate is -15°C, the Tgk of a homopolymer of glycidyl methacrylate is 41°C, and the Tgk of a homopolymer of 2-ethylhexyl acrylate is 42°C. Homopolymer Tgk is -70℃.
[0068] The content of the polymer component when the total weight of the composition for the protective film-forming film is 100 parts by mass is preferably 5 to 80 parts by mass, 8 to 70 parts by mass, 10 to 60 parts by mass, 12 to 55 parts by mass, 14 to 50 parts by mass, or 15 to 45 parts by mass. By setting the content of the polymer component within the above range, excessive swelling and deformation caused by the protective film absorbing the flux cleaner is suppressed, and it becomes easier to maintain the shape of the protective film in the same shape as the chip. In addition, it becomes easier to control the adhesion of the protective film-forming film.
[0069] (1.6.2 Thermosetting components) The curable component (B) cures the protective film-forming film to form a hard protective film. As the curable component, a thermosetting component, an energy ray curable component, or a mixture thereof can be used. When cured by irradiation with energy rays, the protective film-forming film according to this embodiment contains a filler and a colorant, etc., which will be described later, and therefore the light transmittance is reduced. Therefore, for example, when the thickness of the protective film-forming film is increased, the energy ray curing is likely to be insufficient.
[0070] On the other hand, a thermosetting protective film-forming film can be sufficiently cured by heating even if it is thick, so that a protective film with high protective performance can be formed. In addition, a large number of protective film-forming films can be heated and thermally cured at the same time by using a normal heating means such as a heating oven.
[0071] Therefore, in this embodiment, it is preferable that the curable component is thermosetting, that is, the protective film-forming film according to this embodiment is preferably thermosetting.
[0072] Whether or not a protective film-forming film is thermosetting can be determined as follows. First, a protective film-forming film at room temperature (23°C) is heated to a temperature higher than room temperature, and then cooled to room temperature to obtain a protective film-forming film after heating and cooling. Next, when the hardness of the protective film-forming film after heating and cooling is compared with the hardness of the protective film-forming film before heating at the same temperature, if the protective film-forming film after heating and cooling is harder, this protective film-forming film is determined to be thermosetting.
[0073] As the thermosetting component, for example, epoxy resin, thermosetting polyimide resin, unsaturated polyester resin, and mixtures thereof are preferably used. The thermosetting polyimide resin is a general term for low molecular weight, low viscosity monomers or precursor polymers that form polyimide resins by thermal curing. Non-limiting examples of thermosetting polyimide resins are described in, for example, Sen-i-gakkaishi-journal "Sen-i to Kogyo" (Sen-i to Kogyo), Vol. 50, No. 3 (1994), pp. 106-118.
[0074] The epoxy resin as a thermosetting component has the property of forming a three-dimensional network and a strong coating when heated. As such an epoxy resin, various known epoxy resins are used. In this embodiment, the molecular weight (formula weight) of the epoxy resin is preferably 300 or more and less than 50,000, 300 or more and less than 10,000, 300 or more and less than 5,000, or 300 or more and less than 3,000. The epoxy equivalent of the epoxy resin is preferably 50 to 5,000 g / eq, more preferably 100 to 2,000 g / eq, and even more preferably 150 to 1,000 g / eq.
[0075] Specific examples of such epoxy resins include glycidyl ethers of phenols such as bisphenol A, bisphenol F, resorcinol, phenyl novolac, and cresol novolac; glycidyl ethers of alcohols such as butanediol, polyethylene glycol, and polypropylene glycol; glycidyl ethers of carboxylic acids such as phthalic acid, isophthalic acid, and tetrahydrophthalic acid; glycidyl or alkyl glycidyl epoxy resins in which active hydrogen bonded to nitrogen atoms such as aniline isocyanurate is substituted with a glycidyl group; and so-called alicyclic epoxides in which epoxy is introduced by, for example, oxidizing carbon-carbon double bonds in the molecule, such as vinylcyclohexane diepoxide, 3,4-epoxycyclohexylmethyl-3,4-dicyclohexanecarboxylate, and 2-(3,4-epoxy)cyclohexyl-5,5-spiro(3,4-epoxy)cyclohexane-m-dioxane. Other epoxy resins having a biphenyl skeleton, a dicyclohexadiene skeleton, a naphthalene skeleton, and the like can also be used.
[0076] When a thermosetting component is used as the curing component (B), it is preferable to use a curing agent (C) as an auxiliary in combination. A heat-activated latent epoxy resin curing agent is preferable as a curing agent for epoxy resin. A "heat-activated latent epoxy resin curing agent" is a type of curing agent that does not react easily with epoxy resin at room temperature (23°C) and is activated by heating above a certain temperature and reacts with epoxy resin. Methods for activating a heat-activated latent epoxy resin curing agent include a method of generating active species (anions, cations) through a chemical reaction by heating; a method in which the agent is stably dispersed in epoxy resin near room temperature and becomes compatible and dissolved with epoxy resin at high temperatures to start a curing reaction; a method in which a molecular sieve-encapsulated type curing agent is dissolved at high temperatures to start a curing reaction; and a method using microcapsules.
[0077] Of the above-mentioned methods, a method in which the compound is stably dispersed in the epoxy resin at around room temperature, becomes compatible and dissolved in the epoxy resin at high temperatures, and initiates a curing reaction is preferred.
[0078] Specific examples of the heat-activated latent epoxy resin curing agent include various onium salts, dibasic acid dihydrazide compounds, dicyandiamide, amine adduct curing agents, high melting point active hydrogen compounds such as imidazole compounds, etc. These heat-activated latent epoxy resin curing agents can be used alone or in combination of two or more. In this embodiment, dicyandiamide is particularly preferred.
[0079] Phenol resins are also preferred as curing agents for epoxy resins. As phenol resins, condensates of phenols such as alkylphenols, polyhydric phenols, naphthol, and aldehydes, etc., can be used without any particular limitations. Specifically, phenol novolac resins, o-cresol novolac resins, p-cresol novolac resins, t-butylphenol novolac resins, dicyclopentadiene cresol resins, polyparavinylphenol resins, bisphenol A type novolac resins, or modified products thereof, etc. can be used.
[0080] The phenolic hydroxyl groups contained in these phenolic resins can easily undergo addition reaction with the epoxy groups of the above-mentioned epoxy resins upon heating to form a cured product with high impact resistance.
[0081] The content of the curing agent (C) is preferably 0.01-30 parts by mass, 0.1-20 parts by mass, 0.2-15 parts by mass, or 0.3-10 parts by mass, based on 100 parts by mass of the epoxy resin. By making the content of the curing agent (C) equal to or greater than the above lower limit, the network structure of the protective film becomes dense, and the protective film is more likely to be able to protect the workpiece. Also, by making the content of the curing agent (C) equal to or less than the above upper limit, the protective film can adequately absorb the deflux agent, thereby more effectively preventing the solvent contained in the deflux agent from penetrating into the interface between the protective film and the chip.
[0082] When dicyandiamide is used as the curing agent (C), it is preferable to use a curing accelerator (D) in combination. As the curing accelerator, for example, imidazoles (imidazoles in which one or more hydrogen atoms are substituted with groups other than hydrogen atoms) such as 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole are preferable. Among these, 2-phenyl-4,5-dihydroxymethylimidazole is particularly preferable.
[0083] The content of the curing accelerator is preferably 0.01-30 parts by mass, 0.1-20 parts by mass, 0.2-15 parts by mass, or 0.3-10 parts by mass, based on 100 parts by mass of the epoxy resin. By making the content of the curing accelerator (D) equal to or more than the above lower limit, the network structure of the protective film becomes dense, so that the protective film is likely to have the ability to protect the workpiece. Also, by making the content of the curing accelerator (D) equal to or less than the above upper limit, the protective film appropriately absorbs the deflux agent, which further suppresses the solvent contained in the deflux agent from penetrating into the interface between the protective film and the chip.
[0084] The total content of the thermosetting component and the curing agent when the total weight of the composition for protective film-forming film is 100 parts by mass is preferably 3 to 80 parts by mass, 5 to 60 parts by mass, 7 to 50 parts by mass, 9 to 40 parts by mass, or 10 to 30 parts by mass. By making the total content of the thermosetting component and the curing agent equal to or more than the above lower limit, the composition exhibits appropriate tack before curing, and the application work can be stably performed. In addition, after curing, the composition is likely to have the performance of protecting the workpiece as a protective film. By adjusting the degree of curing by making the total content of the thermosetting component and the curing agent equal to or less than the above upper limit, the protective film appropriately absorbs the flux cleaning agent, and the solvent contained in the flux cleaning agent can be more effectively prevented from penetrating into the interface between the protective film and the chip.
[0085] (1.6.3 Energy Ray-Curable Components) When the curable component (B) is an energy ray-curable component, the energy ray-curable component is preferably uncured and preferably has adhesive properties, and more preferably is uncured and has adhesive properties.
[0086] The energy ray curable component is a component that is cured by irradiation with energy rays, and is also a component that imparts film-forming properties, flexibility, and the like to the protective film-forming film.
[0087] As the energy ray-curable component, for example, a compound having an energy ray-curable group is preferable. Examples of such a compound include known compounds.
[0088] (1.6.4 Filler) By containing the filler (E) in the protective film-forming film, the protective film obtained by converting the protective film-forming film into a protective film can easily adjust the thermal expansion coefficient, and by bringing this thermal expansion coefficient closer to the thermal expansion coefficient of the workpiece, the adhesive reliability of the chip with the protective film obtained by using the protective film-forming film is further improved. In addition, by containing the filler (E) in the protective film-forming film, a hard protective film can be obtained, and the moisture absorption rate of the protective film can be reduced, further improving the adhesive reliability of the chip with the protective film.
[0089] The filler (E) may be either an organic filler or an inorganic filler, but is preferably an inorganic filler from the viewpoint of shape stability at high temperatures.
[0090] Preferred inorganic fillers include, for example, powders of silica, alumina, talc, calcium carbonate, red iron oxide, silicon carbide, boron nitride, etc.; beads obtained by sphering these inorganic fillers; surface-modified products of these inorganic fillers; single crystal fibers of these inorganic fillers; glass fibers, etc. Among these, silica and surface-modified silica are preferred.
[0091] In this embodiment, from the viewpoint of dispersibility in the coating agent described later, surface-modified silica is preferred, and surface-modified to reduce reactivity with 2-aminoethanol is preferred. Specifically, surface-modified with a functional group having low polarity is preferred, and modified with a vinyl group is preferred. By using such surface-modified silica, the cohesiveness of the particles of the silica filler is appropriately utilized in the protective film while maintaining dispersibility in the coating agent, and the shear strength of the interface between the protective film and the silicon chip after immersion in 2-aminoethanol tends to improve.
[0092] In this embodiment, the average particle size of the filler is preferably relatively small. Specifically, the average particle size of the filler is preferably 0.02 to less than 1 μm, 0.05 to less than 0.5 μm, or 0.10 to less than 0.4 μm.
[0093] By setting the average particle size of the filler to the above value, it is possible to enhance the effect obtained by using silica whose surface has been modified with a specific functional group.
[0094] In this specification, unless otherwise specified, the term "average particle size" refers to the particle size (D50) at an integrated value of 50% in a particle size distribution curve determined by a laser diffraction scattering method.
[0095] The content of the filler when the total weight of the composition for protective film-forming film is 100 parts by mass is preferably 15 to 80 parts by mass, 30 to 75 parts by mass, 40 to 70 parts by mass, or 45 to 65 parts by mass.
[0096] By setting the lower limit of the content of the filler to the above value, the above-mentioned effect of containing the filler can be more effectively exhibited. Also, by setting the upper limit of the content of the filler to the above value, the adhesive strength of the protective film-forming film to the workpiece can be further improved.
[0097] 1.6.5 Coupling Agents By containing a coupling agent in the protective film-forming film, after the protective film-forming film is cured, the adhesiveness between the protective film and the workpiece can be improved without impairing the heat resistance of the protective film, and the water resistance (moisture and heat resistance) can be improved. As the coupling agent, a silane coupling agent is preferable from the viewpoint of its versatility and cost merit.
[0098] In this embodiment, a silane coupling agent having, as the reactive functional group, an alkyl group such as a methyl group or an ethyl group, an alkoxy group such as a methoxy group or an ethoxy group, a glycidoxy group such as an epoxy group, an amino group, a vinyl group such as a (meth)acryloxy group, a mercapto group, or the like is preferred, and a silane coupling agent having an alkyl group and an alkoxy group is preferred.
[0099] In addition, as the silane coupling agent, an oligomer type silane coupling agent having a molecular weight of 300 or more is preferable rather than a low molecular weight silane coupling agent having a molecular weight of less than 300. By using an oligomer type silane coupling agent, the chemical bond between silicon or the like and the protective film-forming film tends to be relatively strong.
[0100] As a specific silane coupling agent, one having a plurality of alkoxysilyl groups in the molecule (oligomeric silane coupling agent) can be used. For example, epoxy group-containing oligomeric silane coupling agents manufactured by Shin-Etsu Chemical Co., Ltd., trade names "X-41-1053", "X-41-1059A", "X-41-1056", "X-40-2651"; mercapto group-containing oligomeric silane coupling agents "X-41-1818", "X-41-1810", "X-41-1805" and the like can be mentioned. These can be used alone or in combination of two or more. In addition, by using the above-mentioned filler and the above-mentioned silane coupling agent in combination, the shear strength of the interface between the protective film and the silicon chip after immersion in 2-aminoethanol tends to be improved.
[0101] The content of the coupling agent when the total weight of the composition for protective film-forming film is 100 parts by mass is preferably 0.01 to 20 parts by mass, 0.1 to 10 parts by mass, 0.2 to 5 parts by mass, or 0.3 to 3 parts by mass.
[0102] 1.6.6 Colorants The protective film-forming film preferably contains a colorant (G), which conceals the back surface of the workpiece such as a chip, thereby blocking various electromagnetic waves generated in electronic devices and reducing malfunction of the workpiece such as a chip.
[0103] As the colorant (G), for example, known ones such as organic pigments, organic dyes, and inorganic pigments can be used.
[0104] Examples of organic pigments and organic dyes include aminium-based dyes, cyanine-based dyes, merocyanine-based dyes, croconium-based dyes, squalium-based dyes, azulenium-based dyes, polymethine-based dyes, naphthoquinone-based dyes, pyrylium-based dyes, phthalocyanine-based dyes, naphthalocyanine-based dyes, naphtholactam-based dyes, azo-based dyes, condensed azo-based dyes, indigo-based dyes, perinone-based dyes, perylene-based dyes, dioxazine-based dyes, quinacridone-based dyes, isoindolinone-based dyes, quinophthalone-based dyes, pyrrole-based dyes, thioindigo-based dyes, metal complex-based dyes (metal complex dyes), dithiol metal complex-based dyes, indolephenol-based dyes, triarylmethane-based dyes, anthraquinone-based dyes, dioxazine-based dyes, naphthol-based dyes, azomethine-based dyes, benzimidazolone-based dyes, pyranthrone-based dyes, and threne-based dyes. The organic colorant may be composed of one type of material, or may be composed of multiple types of materials.
[0105] Examples of inorganic pigments include carbon black, cobalt-based pigments, iron-based pigments, chromium-based pigments, titanium-based pigments, vanadium-based pigments, zirconium-based pigments, molybdenum-based pigments, ruthenium-based pigments, platinum-based pigments, ITO (indium tin oxide)-based pigments, ATO (antimony tin oxide)-based pigments, etc. Among these, it is particularly preferable to use carbon black.
[0106] The amount of colorant in the protective film-forming film varies depending on the thickness of the protective film-forming film. For example, when the thickness of the protective film-forming film is 40 μm, the content of the colorant is preferably 0.01 to 10 parts by mass, 0.03 to 7 parts by mass, or 0.05 to 4 parts by mass when the total weight of the composition for the protective film-forming film is 100 parts by mass.
[0107] The average particle size of the colorant is preferably 1 to 500 nm, 3 to 100 nm, or 5 to 50 nm. When the average particle size of the colorant is within the above range, it is easy to control the light transmittance within a desired range.
[0108] 1.6.7 Other Additives The composition for the protective film-forming film may contain other additives, such as a photopolymerization initiator, a crosslinking agent, a plasticizer, an antistatic agent, an antioxidant, a gettering agent, a tackifier, a release agent, etc., within the range that does not impair the effects of the present invention.
[0109] (2. Protective film forming sheet) The sheet for forming a protective film according to this embodiment has the above-mentioned protective film-forming film and a release film disposed on at least one main surface of the protective film-forming film. The release film is peeled off when the protective film-forming film is used.
[0110] The protective film-forming sheet 51 shown in Figure 2A has a configuration in which a first release film 21 supporting the protective film-forming film 10 is arranged on one main surface 10a of the protective film-forming film 10, and a second release film 22 is arranged on the other main surface 10b.
[0111] On the other hand, the protective film forming sheet 52 shown in Figure 2B has a configuration in which a first release film 21 supporting the protective film forming film 10 is arranged on one main surface 10a of the protective film forming film 10, and no release film is arranged on the other main surface 10b.
[0112] The protective film forming sheet of this embodiment is used to form a protective film on the workpiece or a processed product of the workpiece by attaching a protective film forming film to the workpiece when the workpiece is processed, and turning the protective film forming film into a protective film.
[0113] The protective film-forming sheet may be in the form of a long sheet having a length in the longitudinal direction that is very long relative to the length in the lateral direction, or in the form of a sheet roll in which such a long sheet is wound up.
[0114] Furthermore, the protective film forming sheet may be a protective film forming sheet that is punched so that the protective film forming film to be attached to the workpiece has a predetermined closed shape. The predetermined closed shape is not particularly limited, but it is preferably approximately the same shape as the workpiece to be attached.
[0115] (2.1 Release film) The release film is a film that can support the protective film-forming film in a releasable manner. The release film may be composed of one layer (single layer) or two or more layers of substrate, and the surface of the substrate may be subjected to a release treatment in order to control the releasability. That is, the surface of the substrate may be modified, or a material (release agent layer) not derived from the substrate may be formed on the surface of the substrate.
[0116] The substrate is not particularly limited as long as it is a material that can support the protective film-forming film until it is attached to the workpiece, and is usually composed of a film primarily made of a resin-based material (hereinafter referred to as a "resin film").
[0117] Specific examples of the resin film include polyethylene film, polypropylene film, polybutene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polyethylene naphthalate film, polybutylene terephthalate film, polyurethane film, ethylene vinyl acetate copolymer film, ionomer resin film, ethylene-(meth)acrylic acid copolymer film, ethylene-(meth)acrylic acid ester copolymer film, polystyrene film, polycarbonate film, polyimide film, and fluororesin film. Crosslinked films of these films are also used. Furthermore, laminated films of these films may be used. In this embodiment, a polyethylene terephthalate film is preferred from the viewpoints of environmental safety, cost, and the like.
[0118] The above resin film may contain various additives such as a colorant, a flame retardant, a plasticizer, an antistatic agent, a lubricant, and a filler.
[0119] The release agent layer is obtained by applying a coating agent containing a composition for a release agent layer to one side of a substrate, and then drying and curing the coating. The composition for a release agent layer is not particularly limited as long as it is a material that can impart releasability from the protective film-forming film to the substrate. In this embodiment, the composition for a release agent layer is preferably, for example, an alkyd-based release agent, a silicone-based release agent, a fluorine-based release agent, an unsaturated polyester-based release agent, a polyolefin-based release agent, or a wax-based release agent, and among these, a silicone-based release agent is preferable.
[0120] The thickness of the release film is not particularly limited, but is preferably 15 to 100 μm, more preferably 25 to 80 μm, and even more preferably 35 to 60 μm.
[0121] In addition, when release films are formed on both main surfaces of the protective film-forming film, it is preferable to make the release strength of one release film larger to make it a heavy release type release film, and to make the release strength of the other release film smaller to make it a light release type release film.
[0122] (3. Composite sheet for forming protective film) The composite sheet for forming a protective film according to this embodiment has the above-mentioned protective film-forming film and a support sheet that supports the protective film-forming film. The configuration of the support sheet is not particularly limited as long as it can control the adhesion and peelability to a degree that a workpiece with a protective film can be obtained. For example, the support sheet may be made of only a substrate having a predetermined rigidity as described below. In this embodiment, in order to make it easier to control the adhesion and peelability, the support sheet is preferably an adhesive sheet having a substrate and an adhesive layer.
[0123] 3A has a configuration including an adhesive sheet 4 formed by laminating an adhesive layer 42 on one surface of a substrate 41, a protective film-forming film 10 laminated on the adhesive layer 42 side of the adhesive sheet 4, and a jig adhesive layer 5 laminated on the peripheral portion of the protective film-forming film 10 on the side opposite to the adhesive sheet 4. The jig adhesive layer 5 is a layer for adhering the protective film-forming composite sheet 61 to a jig such as a ring frame. Therefore, the adhesive sheet is a support sheet.
[0124] In addition, the composite sheet 62 for forming a protective film shown in Figure 3B has a configuration including an adhesive sheet 4 having an adhesive layer 42 laminated on one side of a substrate 41, and a protective film forming film 10 laminated on the adhesive layer 42 side of the adhesive sheet 4.
[0125] The composite sheet for forming a protective film in this embodiment is attached to a workpiece when the workpiece is processed to hold the workpiece, and is also used to turn a protective film forming film into a protective film and form a protective film on the workpiece or a processed product of the workpiece.
[0126] Specifically, it is used to hold a wafer as a workpiece during dicing of the wafer, and to form a protective film on chips as the workpiece obtained by dicing, but is not limited to this.
[0127] (3.1 Adhesive sheet) The adhesive sheet 4 of the composite sheet for forming a protective film according to this embodiment is configured to include a base material 41 and an adhesive layer 42 laminated on one surface of the base material 41.
[0128] (3.1.1. Base material) The base material 41 of the adhesive sheet 4 is not particularly limited in terms of its constituent material, so long as it is suitable for processing the workpiece, such as dicing and expanding a wafer, and is usually composed of a film primarily made of a resin-based material (hereinafter referred to as a "resin film").
[0129] Specific examples of the resin film include polyethylene films such as low-density polyethylene (LDPE) film, linear low-density polyethylene (LLDPE) film, and high-density polyethylene (HDPE) film, polyolefin films such as polypropylene film, polybutene film, polybutadiene film, polymethylpentene film, ethylene-norbornene copolymer film, and norbornene resin film; ethylene copolymer films such as ethylene-vinyl acetate copolymer film, ethylene-(meth)acrylic acid copolymer film, and ethylene-(meth)acrylic acid ester copolymer film; polyvinyl chloride films such as polyvinyl chloride copolymer film; polyester films such as polyethylene terephthalate film and polybutylene terephthalate film; polyurethane film; polyimide film; polystyrene film; polycarbonate film; and fluororesin film. Modified films such as crosslinked films and ionomer films are also used. The substrate 41 may be a film made of one of these, or may be a laminated film made by combining two or more of these. In this embodiment, polypropylene films and polybutylene terephthalate films are preferred from the viewpoint of heat resistance when the composite sheet for forming a protective film is used in a process in which it is heated.
[0130] The above-mentioned resin film may be subjected to a surface treatment such as an oxidation method or a roughening method, or a primer treatment, on one or both sides as desired, for the purpose of improving adhesion to the pressure-sensitive adhesive layer 42 laminated on the surface of the resin film. Examples of the oxidation method include corona discharge treatment, plasma discharge treatment, chromium oxidation treatment (wet), flame treatment, hot air treatment, ozone treatment, and ultraviolet irradiation treatment, and examples of the roughening method include sandblasting and thermal spraying treatment.
[0131] The above resin film may contain various additives such as a colorant, a flame retardant, a plasticizer, an antistatic agent, a lubricant, and a filler.
[0132] The thickness of the substrate 41 is not particularly limited as long as the composite sheet for forming a protective film can function properly in each process in which it is used, and is preferably in the range of 20 to 200 μm, more preferably 40 to 170 μm, and particularly preferably 50 to 140 μm.
[0133] (3.1.2. Adhesive Layer) The adhesive layer 42 of the adhesive sheet 4 of the composite sheet for forming a protective film according to this embodiment may be composed of a non-energy ray curable adhesive or an energy ray curable adhesive. As the non-energy ray curable adhesive, those having the desired adhesive strength and removability are preferable, and for example, acrylic adhesives, rubber adhesives, silicone adhesives, urethane adhesives, polyester adhesives, polyvinyl ether adhesives, etc. can be used. Among these, acrylic adhesives are preferable because they have high adhesion to the protective film-forming film 10 and can effectively suppress the workpiece or the processed product of the workpiece from falling off during a dicing process or the like. In addition, acrylic adhesives are preferable from the viewpoint of easily controlling the pick-up suitability of the processed product of the workpiece with the protective film.
[0134] On the other hand, the adhesive strength of an energy ray-curable adhesive decreases when irradiated with energy rays, so that when it is desired to separate the workpiece or a processed product of the workpiece from the adhesive sheet 4, they can be easily separated by irradiating them with energy rays.
[0135] The energy ray curable adhesive constituting the adhesive layer 42 may be one whose main component is a polymer having energy ray curability, or may be one whose main component is a mixture of a polymer not having energy ray curability and an energy ray curable monomer and / or oligomer.
[0136] Examples of the energy ray-curable polymer include (meth)acrylic acid ester (co)polymers having an energy ray-curable group introduced therein. Examples of the energy ray-curable monomer and / or oligomer include esters of polyhydric alcohol and (meth)acrylic acid. The energy ray-curable adhesive may contain additives such as photopolymerization initiators and crosslinking agents in addition to the energy ray-curable components.
[0137] The thickness of the adhesive layer 42 is not particularly limited as long as it can function appropriately in each process in which the composite sheet for forming a protective film 3 is used. Specifically, the thickness of the adhesive layer is preferably 1 to 50 μm, 2 to 30 μm, 2 to 20 μm, 3 to 10 μm, or 3 to 8 μm.
[0138] The adhesive constituting the jig adhesive layer 5 is preferably one having the desired adhesive strength and removability, and for example, an acrylic adhesive, a rubber adhesive, a silicone adhesive, a urethane adhesive, a polyester adhesive, a polyvinyl ether adhesive, etc. can be used. Among these, an acrylic adhesive is preferred because it has high adhesion to a jig such as a ring frame and can effectively prevent the composite sheet for forming a protective film 3 from peeling off from the ring frame, etc. during a dicing process, etc. In addition, a substrate as a core material may be interposed in the middle of the thickness direction of the jig adhesive layer 5.
[0139] The thickness of the jig pressure-sensitive adhesive layer 5 is preferably 5 to 200 μm, particularly preferably 10 to 100 μm, from the viewpoint of adhesion to a jig such as a ring frame.
[0140] (4. Method for producing protective film-forming film and protective film-forming sheet) The method for producing the protective film-forming film is not particularly limited. The film is produced using the above-mentioned composition for protective film-forming film, or a composition obtained by diluting the composition for protective film-forming film with a solvent (the above two compositions are referred to as "coating agent"). The coating agent is prepared by mixing the components constituting the composition for protective film-forming film by a known method.
[0141] The obtained coating agent is applied to the release surface of the first release film using a coating machine such as a roll coater, a knife coater, a roll knife coater, an air knife coater, a die coater, a bar coater, a gravure coater, a curtain coater, etc., and dried as necessary to form a protective film-forming film on the first release film. As a result, a protective film-forming sheet as shown in FIG. 2B is obtained.
[0142] Moreover, by further laminating the release surface of a second release film to the exposed surface of the protective film-forming film formed on the first release film, the sheet for forming a protective film shown in FIG. 2A is obtained.
[0143] Furthermore, if necessary, the sheet for forming a protective film may be punched. The punching process may be performed, for example, as follows. As shown in Figs. 4A and 4B, a punch (not shown) is used to make a cut 14 from the surface of the sheet for forming a protective film 51, 52 on the side of the protective film-forming film 10, penetrating the protective film-forming film 10 and reaching a part of the surface of the first release film 21. Such an operation of making a cut to reach a part of the surface and not cutting completely is called half-cutting. As a result, the cut 14 is formed in a part of the surface of the sheet for forming a protective film 10 so as to have a predetermined closed shape.
[0144] By forming the cuts, the protective film-forming film is divided into a protective film-forming film 16 that has been cut into a predetermined closed shape and an unnecessary portion 17 that is continuous with the periphery thereof, so that the unnecessary portion may be removed.
[0145] (5. Method for producing composite sheet for forming protective film) The method for producing the composite sheet for forming a protective film is not particularly limited. For example, the composite sheet for forming a protective film can be produced by separately producing a first laminate including a protective film-forming film and a second laminate including a pressure-sensitive adhesive sheet as a support sheet, and then laminating the protective film-forming film and the pressure-sensitive adhesive sheet using the first laminate and the second laminate.
[0146] The first laminate can be produced by the same method as the above-mentioned sheet for forming a protective film. That is, a protective film-forming film is formed on the release surface of the first release film, and the release surface of the second release film is bonded to the exposed surface of the protective film-forming film.
[0147] In the first laminate, similarly to the above-mentioned sheet for forming a protective film, half-cutting may be performed as necessary to make the protective film-forming film and the second release film into a desired shape, for example, a circle, etc. In this case, the excess parts of the protective film-forming film and the second release film generated by half-cutting may be appropriately removed.
[0148] On the other hand, to manufacture the second laminate, first, an adhesive composition constituting the adhesive layer, or a composition obtained by diluting the adhesive composition with a solvent (these two compositions are referred to as "coating agents"). Next, the coating agent is applied to the release surface of a third release film and dried as necessary to form an adhesive layer on the third release film. After that, a substrate is attached to the exposed surface of the adhesive layer to obtain a laminate (second laminate) consisting of an adhesive sheet consisting of the substrate and adhesive layer, and the third release film.
[0149] Here, when the adhesive layer is made of an energy ray curable adhesive, the adhesive layer may be cured by irradiating the adhesive layer with energy rays at this stage, or the adhesive layer may be cured after lamination with the protective film-forming film. In addition, when the adhesive layer is cured after lamination with the protective film-forming film, the adhesive layer may be cured before the dicing step, or the adhesive layer may be cured after the dicing step.
[0150] As the energy beam, ultraviolet rays, electron beams, etc. are usually used. The irradiation amount of the energy beam varies depending on the type of the energy beam. For example, in the case of ultraviolet rays, the light amount is 50 to 1000 mJ / cm. 2 is preferable, and particularly 100 to 500 mJ / cm 2 In the case of electron beams, the intensity is preferably about 10 to 1000 krad.
[0151] Once the first laminate and the second laminate are obtained in the above manner, the second release film of the first laminate is peeled off, and the third release film of the second laminate is peeled off, and the protective film-forming film exposed in the first laminate is bonded to the adhesive layer of the adhesive sheet exposed in the second laminate.
[0152] The adhesive sheet may be cut as necessary to a desired shape, for example, a circle having a diameter larger than that of the protective film-forming film. In this case, the excess part of the adhesive sheet generated by cutting may be appropriately removed. In addition, the protective film-forming film and the adhesive layer may be formed into a circle having the same diameter.
[0153] In this way, a composite sheet for forming a protective film is obtained, which comprises an adhesive sheet having an adhesive layer laminated on a substrate, a protective film-forming film laminated on the adhesive layer side of the adhesive sheet, and a first release film laminated on the protective film-forming film on the side opposite to the adhesive sheet. If necessary, after peeling off the first release film, a jig adhesive layer is formed on the peripheral portion of the exposed protective film-forming film or adhesive layer.
[0154] (6. Device Manufacturing Method) As an example of a method for manufacturing a device using the protective film-forming film of this embodiment, a method for manufacturing a mounting substrate on which a protective film-coated chip obtained by processing a wafer to which a protective film-forming film is attached is mounted will be described.
[0155] The method for manufacturing the device according to this embodiment includes at least the following steps 1 to 6. Step 1: A step of attaching a protective film-forming film provided in a protective film-forming sheet or a protective film-forming film provided in a protective film-forming composite sheet to the back surface of a wafer; Step 2: The process of making the attached protective film into a protective film Step 3: A step of dividing the wafer having the protective film or protective film-forming film on the back surface into individual chips to obtain a plurality of chips having the protective film or protective film-forming film. Step 4: A step of placing the protective film or the chip with the protective film-forming film on the substrate in contact with the flux. Step 5: Heating the protective film or the chip with the protective film-forming film arranged on the substrate and the substrate Step 6: A step of cleaning the substrate on which the protective film-coated chip is arranged with a flux cleaner.
[0156] As is clear from the above, step 2 may be performed before steps 3 and 4, or after step 3 and before step 4, or after steps 3 and 4, but before step 6.
[0157] A method for manufacturing the device, which includes the above steps 1 to 6, will be described with reference to FIGS.
[0158] 5A, the protective film-forming film 10 of the protective film-forming sheet 51 is attached to the back surface of the wafer 6 (step 1). If necessary, the second release film 22 may be peeled off.
[0159] As shown in FIG. 5B, the protective film-forming film 10 of the composite sheet 61 for forming a protective film is attached to the wafer 6 (step 1). At this time, the outer periphery of the protective film-forming film 10 may be fixed by a ring frame 7. In this embodiment, as shown in FIG. 3A, the jig adhesive layer 5 is provided on the outer periphery of the protective film-forming film 10, so the jig adhesive layer 5 is attached to the ring frame 7. The wafer 6 is attached to the surface of the protective film-forming film 10 opposite to the surface attached to the adhesive layer 42. When attaching the protective film-forming film 10 to the wafer 6, the protective film-forming film 10 may be heated as desired to exhibit adhesiveness.
[0160] Thereafter, the attached protective film-forming film 10 is made into a protective film to form a protective film (step 2), thereby obtaining a wafer 6 with a protective film. When the protective film-forming film 10 is thermosetting, the protective film-forming film 10 may be heated at a predetermined temperature for an appropriate time. When the protective film-forming film 10 is energy ray-curable, energy rays may be applied from the adhesive sheet 4 or release film side.
[0161] The protective film-forming film 10 may be cured after the dicing step, or the chip with the protective film-forming film attached may be picked up from the adhesive sheet and then the protective film-forming film may be cured.
[0162] Next, if necessary, the protective film-coated wafer 6 and ring frame 7 obtained by converting the protective film-forming film 10 of the protective film-forming sheet 51 shown in Figure 5A into a protective film are attached to a known dicing sheet 22, and the protective film-coated wafer 6 is diced to obtain a chip having the protective film 1 shown in Figure 6 (protective film-coated chip 70) (step 3).
[0163] Furthermore, by using a known method, the protective film-forming film 10 of the composite sheet 61 for forming a protective film shown in FIG. 5B is made into a protective film to obtain a wafer 6 with a protective film, and then the wafer 6 with a protective film is diced to obtain a chip having a protective film 1 (chip 70 with a protective film) (step 3).
[0164] Thereafter, the dicing sheet or adhesive sheet is expanded in a planar direction as required, and the chip with the protective film is picked up from the dicing sheet by a suction collet or the like.
[0165] The picked up chips with protective film may be transported to the next process, or may be temporarily stored in a tray, tape, or the like, and transported to the next process after a predetermined period of time.
[0166] The protective film-coated chip 70 transported to the next process is transported to the substrate 50 by the suction collet C as shown in Fig. 7, and is detached from the suction collet C at the terminal portion on the substrate, and is arranged at a position where the connection electrodes such as bumps can be connected to the terminal portions such as pads (process 4). At this time, flux is applied to at least one of the connection electrodes of the protective film-coated chip and the terminal portions on the substrate by a known method.
[0167] The chip with the protective film arranged at a predetermined position on the substrate is subjected to a heat treatment (for example, a reflow treatment) together with the flux (step 5). The reflow treatment conditions are preferably, for example, a maximum heating temperature of 180 to 350° C. and a reflow time of 2 to 10 minutes.
[0168] In the reflow process, the flux removes dirt and oxide film adhering to the convex electrodes of the protective film-coated chip and the terminals on the board, and in a state in which the surface tension of the solder is reduced, the convex electrodes 6b of the protective film-coated chip 70 melt and are electrically and mechanically joined to the terminals on the board, and the protective film-coated chip 70 is mounted on the board. Although most of the flux volatilizes by the end of the reflow process, some of the flux remains as flux residue near the joint between the protective film-coated chip and the board.
[0169] In order to remove the flux residue, in this embodiment, the substrate on which the chips with protective film are mounted is cleaned with a flux cleaner (step 6). Specifically, the substrate is cleaned by immersing the substrate in the flux cleaner or spraying the flux cleaner onto the substrate. As the flux cleaner, an alcohol-based cleaner or an amine-based cleaner is preferable, an amine-based and alcohol-based flux cleaner is more preferable, and a flux cleaner containing 2-aminoethanol is particularly preferable.
[0170] In this embodiment, since the protective film has the above-mentioned physical properties, even if flux cleaning is performed, penetration of 2-aminoethanol into the interface between the protective film and the silicon chip can be suppressed, and thus floating or peeling at the interface can be effectively suppressed in a reliability test.
[0171] The method for producing the device may include, in addition to the above-mentioned steps 1 to 6, a step (step 7) of performing laser marking on the protective film or the protective film-forming film.
[0172] Step 7 is performed after step 2 and before step 5. In this embodiment, step 7 is preferably performed before steps 3 and 4.
[0173] By carrying out the laser marking, it becomes possible to identify whether the chip is provided with a protective film-forming film or a protective film after the laser marking has been carried out.
[0174] In the laser marking, the marking may be performed by scraping off the surface of the protective film-forming film or protective film by laser irradiation, or the marking may be performed by increasing the volume of the protective film-forming film or protective film by laser irradiation to form a convex portion. The laser marking may be performed using a known laser marking device.
[0175] (7. Modifications) A jig adhesive layer similar to the jig adhesive layer 5 of the composite sheet 61 for forming a protective film described above may be separately provided on the peripheral portion of the adhesive layer 42 of the adhesive sheet 4 of the composite sheet 62 for forming a protective film.
[0176] Further, a release film may be laminated on the surface of the protective film-forming film 10 side of the protective film-forming composite sheets 61 and 62 in order to protect the protective film-forming film until use.
[0177] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and may be modified in various aspects within the scope of the present invention. EXAMPLES
[0178] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples.
[0179] (Preparation of protective film forming sheet) [First release film (heavy release type release film)] Lintec Corporation's "SP-PET502150" (thickness 50 μm) was used.
[0180] [Second release film (light release type release film)] Lintec's "SP-PET381130 (thickness 38 μm)" was used.
[0181] [Coating agent containing a composition for forming a protective film] The following components were mixed in the compounding ratio (solid content equivalent) shown in Table 1, and diluted with methyl ethyl ketone to a solid content concentration of 50 mass % to prepare a coating agent. (A) Polymer Component (A-1): (meth)acrylic acid ester copolymer obtained by copolymerizing 85 parts by mass of methyl acrylate and 15 parts by mass of 2-hydroxyethyl acrylate (weight average molecular weight: 400,000, glass transition temperature: 6°C) (A-2): (meth)acrylic acid ester copolymer obtained by copolymerizing 15 parts by mass of n-butyl acrylate, 62 parts by mass of methyl acrylate, 13 parts by mass of glycidyl methacrylate, and 10 parts by mass of 2-hydroxyethyl acrylate (weight average molecular weight: 400,000, glass transition temperature: -1°C) (B) Curing component (thermosetting component) (B-1) Bisphenol A type epoxy resin (Mitsubishi Chemical Corporation, jER828, epoxy equivalent 184-194g / eq) (B-2) Bisphenol A type epoxy resin (Mitsubishi Chemical Corporation, jER1055, epoxy equivalent 800-900g / eq) (B-3) Dicyclopentadiene type epoxy resin (manufactured by Dainippon Ink and Chemicals, Epicron HP-7200HH, softening point 88-98°C, epoxy equivalent 255-260g / eq) (C) Hardener: Dicyandiamide (DICY7, manufactured by Mitsubishi Chemical Corporation) (D) Curing accelerator: 2-phenyl-4,5-dihydroxymethylimidazole (manufactured by Shikoku Chemical Industry Co., Ltd., Curesol 2PHZ-PW) (E) Filler (E-1) Epoxy group-modified spherical silica filler (manufactured by Admatechs Co., Ltd., SC2050MA, average particle size 0.5 μm) (E-2) Vinyl group-modified spherical silica filler (Admatechs Co., Ltd., SC105G-MMQ, average particle size 0.3 μm) (F) Silane coupling agent: an oligomer type silane coupling agent containing an epoxy group, a methyl group, and a methoxy group (manufactured by Shin-Etsu Silicone Co., Ltd., X-41-1056, epoxy equivalent 280 g / eq) (G) Coloring agent Organic colorants: A mixture of phthalocyanine blue pigment (Pigment Blue 15:3 fixed with three times the mass of styrene-acrylic resin), isoindolinone yellow pigment (Pigment Yellow 139 fixed with three times the mass of styrene-acrylic resin), and diketopyrrolopyrrole red pigment (Pigment Red 264 fixed with three times the mass of styrene-acrylic resin) in a ratio of 38:18:44 (blue:yellow:red, by mass).
[0182] [Table 1]
[0183] The prepared composition for protective film-forming film was applied to the release-treated surface of the first release film, and dried at 100°C for 2 minutes to form a protective film-forming film with a thickness of 40 μm. Then, the second release film was attached to the protective film-forming film to obtain a three-layered sheet for protective film-forming film in which release films were formed on both sides of the protective film-forming film. The attachment conditions were a temperature of 60°C, a pressure of 0.4 MPa, and a speed of 1 m / min.
[0184] The obtained sheet for forming a protective film was subjected to the following measurements and evaluations.
[0185] (Shear strength of the interface between the protective film and the silicon chip after immersion in 2-aminoethanol) A dicing tape (Adwill D-676H, manufactured by Lintec Corporation) was attached to the polished surface of a #2000 polished silicon wafer (diameter 200 mm, thickness 350 μm). The silicon wafer was diced into 30 mm × 30 mm size pieces using a dicing device (DFD6362, manufactured by Disco Corporation), and the dicing tape was peeled off to obtain silicon chips.
[0186] The protective film-forming sheets of the examples and comparative examples were cut into a width of 5 mm and a length of 30 mm. The second release film was peeled off from the cut protective film-forming sheet, and the protective film-forming film exposed at the center of the obtained silicon chip (30 mm x 30 mm) was attached while being heated to 70 ° C. at a speed of 0.3 m / min. Next, the first release film was peeled off, and the protective film-forming film was cured by heating (130 ° C., 2 hours), and a chip with a protective film for shear strength measurement was obtained in which a protective film with a width of 5 mm was formed at the center of the silicon chip (30 mm x 30 mm).
[0187] The obtained chip with protective film was immersed in 2-aminoethanol filled in the cleaning tank of an ultrasonic cleaner (UT-206H, manufactured by Sharp Corporation) and irradiated with ultrasonic waves at a frequency of 37 kHz for 15 minutes at 23° C. After ultrasonic irradiation, the chip with protective film was removed from the 2-aminoethanol, the 2-aminoethanol adhering to the surface was washed off with distilled water for 2 seconds, the distilled water was wiped off, and the chip was left to stand for 10 minutes, and the shear strength at room temperature (23° C.) was measured by the method described below.
[0188] Using a universal bond tester (Nordson Advanced Technology's "DAGE4000"), under conditions of 23°C, a force was applied to only the protective film of the chip with protective film (at a height of 5 μm from the interface between the protective film and the chip) with a shear tool at a speed of 200 μm / s in the direction of the surface of the protective film, with the direction of movement of the shear tool perpendicular to the short side of the protective film. Then, the force applied from the end of the chip with protective film to 15 mm (halfway point of the chip) was measured, and the first half of the measured values from the start of the measurement to 5 mm were omitted, and the maximum value was obtained from the remaining latter half of the measured values (between 5 mm and 15 mm). This measurement was performed on three samples in each example and comparative example, and the average of the maximum values obtained was taken as the shear strength (N / 5 mm). The results are shown in Table 2.
[0189] (Contact angle of 2-aminoethanol on protective film surface) The second release film was peeled off from the protective film-forming sheet of the examples and comparative examples, and the protective film-forming film exposed on the polished surface of a silicon wafer (200 mm diameter, 350 μm thick) polished with #2000 was attached while heating to 70 ° C. at a speed of 0.3 m / min. The first release film was peeled off from the protective film-forming film to expose the protective film-forming film. The silicon wafer with the protective film-forming film attached was heated in an oven under atmospheric conditions at 130 ° C. for 2 hours to turn the protective film-forming film into a protective film, thereby producing a wafer with a protective film. For the wafer with a protective film, the contact angle of 2-aminoethanol on the protective film surface was measured as follows. In an environment of 23 ° C. and relative humidity 50%, 0.2 μL of 2-aminoethanol was dropped on the surface of the protective film using an automatic contact angle meter (KRUSS "DSA100"). This measurement was carried out for 10 samples in each Example and Comparative Example, and the average of the measured values was taken as the contact angle of 2-aminoethanol. The results are shown in Table 2.
[0190] (Change in gloss of protective film surface before and after immersion in 2-aminoethanol) The second release film was peeled off from the protective film-forming sheet of each of the examples and comparative examples, and the exposed protective film-forming film was attached to the polished surface of a #2000 polished silicon wafer (200 mm diameter, 350 μm thickness) while heating at a speed of 0.3 m / min to 70° C. The first release film was peeled off from the protective film-forming film to expose the protective film-forming film.
[0191] The silicon wafer with the protective film-forming film attached was heated in an oven under an atmospheric air at 130°C for 2 hours to convert the protective film-forming film into a protective film, thereby producing a wafer with a protective film. The gloss value of the wafer with the protective film was measured at room temperature (23°C) before immersion in 2-aminoethanol by the method described below.
[0192] In addition, the wafer with the protective film was immersed in 2-aminoethanol filled in the cleaning tank of an ultrasonic cleaner (UT-206H, manufactured by Sharp Corporation) and irradiated with ultrasonic waves at a frequency of 37 kHz for 15 minutes at 23° C. After the ultrasonic irradiation, the chip with the protective film was removed from the 2-aminoethanol, the 2-aminoethanol adhering to the surface was washed off with distilled water for 2 seconds, the distilled water was wiped off, and the chip was left to stand for 10 minutes, and the gloss value of the wafer with the protective film after immersion in 2-aminoethanol at room temperature (23° C.) was measured by the method described below.
[0193] Using a glossmeter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "VG 2000"), a light beam was incident on the surface of the protective film opposite to the surface in contact with the wafer, and the specular gloss was measured in accordance with JIS Z 8741, and the value of the specular gloss was taken as the gloss value of the protective film. The angles of incidence were 20°, 45°, 60°, and 85°. This measurement was performed on three wafers with protective film in each Example and Comparative Example before and after immersion in 2-aminoethanol, and the average of the 12 gloss values before immersion was taken as the gloss value before immersion in 2-aminoethanol, and the average of the 12 gloss values after immersion was taken as the gloss value after immersion in 2-aminoethanol.
[0194] The gloss change rate before and after immersion in 2-aminoethanol was calculated from the gloss value before and after immersion in 2-aminoethanol [(gloss value after immersion in 2-aminoethanol / gloss value before immersion in 2-aminoethanol)×100]. The results are shown in Table 2.
[0195] (Young's modulus and breaking elongation of protective film after immersion in 2-aminoethanol) A plurality of the prepared protective film-forming films were laminated to prepare a laminate of protective film-forming films having a total thickness of 200 μm. This laminate was heated at 130° C. for 2 hours to harden the protective film-forming films, thereby obtaining a laminate of protective films.
[0196] The obtained laminate of protective films was punched (cut) into a size of 15 mm x 50 mm to prepare a measurement sample. The prepared measurement sample was immersed in 2-aminoethanol filled in the cleaning tank of an ultrasonic cleaner (UT-206H, manufactured by Sharp Corporation) and irradiated with ultrasonic waves of 37 kHz frequency at 23 ° C for 15 minutes. After ultrasonic irradiation, the chip with protective film was removed from the 2-aminoethanol, the 2-aminoethanol attached to the surface was washed off with distilled water for 2 seconds, the distilled water was wiped off, and the chip was left to stand for 10 minutes, and the Young's modulus of the measurement sample at room temperature (23 ° C) was measured by the method described below.
[0197] After immersion, the measurement samples were subjected to a tensile test in accordance with JIS K 7127 using a precision universal testing machine (manufactured by Shimadzu Corporation, called "Autograph AG-IS") with a chuck distance of 30 mm (i.e., 10 mm on both ends of the test sample were chucked (non-measured)), at a tensile speed of 50 mm / min, in an environment of 23°C and relative humidity of 50%, to measure Young's modulus (MPa). The results are shown in Table 1.
[0198] In addition, when measuring the Young's modulus of the measurement sample, the breaking elongation (%) of the measurement sample after immersion was calculated from the elongation of the measurement sample when it broke. The results are shown in Table 2. Note that, when the length of the measurement sample in the tensile direction at the time when the measurement sample was held (chucked) at two points 30 mm apart was used as a reference, and the elongation from the reference when the measurement sample was pulled to break was ΔL mm, the breaking elongation was calculated by the following formula. Breaking elongation (%) = [ΔL (mm) / 30 (mm)] × 100
[0199] (Adhesion reliability after flux cleaning) First, the second release film was peeled off from the protective film-forming sheet of the examples and comparative examples, and the protective film-forming film exposed on the polished surface of a silicon wafer (200 mm diameter, 350 μm thick) polished with #2000 was attached while being heated to 70 ° C. at a speed of 0.3 m / min. The first release film was peeled off from the protective film-forming film to expose the protective film-forming film. The silicon wafer with the protective film-forming film attached was heated in an oven under an atmospheric atmosphere at 130 ° C. for 2 hours, and the protective film-forming film was made into a protective film, to produce a wafer with a protective film.
[0200] Next, a dicing tape (Adwill D-676H manufactured by Lintec Corporation) was attached to the surface of the protective film, and the silicon wafer with the protective film was diced into pieces of 3 mm x 3 mm using a dicing device (DFD6362 manufactured by Disco Corporation), and then peeled off from the dicing tape to obtain silicon chips with the protective film.
[0201] The adhesion reliability of the protective film was evaluated by simulating the process when semiconductor chips are mounted, using chips with protective film after cleaning with 2-aminoethanol as a flux cleaner. That is, 25 chips with protective film after cleaning with 2-aminoethanol were placed in a thermal shock device (ESPEC Corp.'s "TSE-11-A") and held at -65°C for 10 minutes, followed by 150°C for 10 minutes, and the thermal cycle was repeated 1000 times.
[0202] Next, all the chips with protective film were removed from the thermal shock chamber, and the presence or absence of lifting or peeling at the joint between the silicon chip and the protective film, and the presence or absence of cracks in the silicon chip were examined using a scanning ultrasonic deep flaw detector (Sonoscan's "D9600"). TM This was confirmed by observing the cross section of the semiconductor chip with protective film using a "CSAM". The number of protective film-covered chips in which at least one of the above-mentioned lifting / peeling and cracks had occurred was then counted, and chips with this number (NG number) of one or less were judged as passing the reliability test (A), and chips with two or more were judged as failing the reliability test (B). The results are shown in Table 2.
[0203] [Table 2]
[0204] From Table 2, it was confirmed that when the shear strength of the interface between the protective film and the silicon chip after immersion in 2-aminoethanol is 33 N / 5 mm or more, the reliability of the chip with the protective film is high. [Explanation of symbols]
[0205] 1...Protective film 51, 52...Protective film forming sheet 10...Protective film forming film 21…First release film 22...Second release film 61, 62...Composite sheet for forming protective film 10...Protective film forming film 4...Adhesive sheet 70…Chip with protective film
Claims
1. A protective film-forming film for forming a protective film, A protective film having a shear strength of the interface between the protective film and the silicon chip after immersion in 2-aminoethanol, measured by the following method, of 33 N / 5 mm or more. A silicon chip with a protective film having a width of 5 mm and a length of 30 mm is immersed in 2-aminoethanol in an ultrasonic cleaner and is irradiated with ultrasonic waves having a frequency of 37 kHz for 15 minutes at 23° C. After the ultrasonic irradiation, the 2-aminoethanol is removed from the silicon chip with the protective film. A force is applied only to the protective film at a speed of 200 μm / s in the surface direction of the protective film by using a shear tool with the direction of travel of the shear tool perpendicular to a 5 mm width of the protective film. The force applied from the end of the protective film-coated silicon chip to 15 mm is measured, and the first half of the measured values from the start of measurement to 5 mm is excluded from the measured values, and the maximum value of the remaining second half of the measured values is calculated, and the average value is taken as the shear strength (N / 5 mm).
2. 2. The protective film according to claim 1, wherein the contact angle of the protective film surface with 2-aminoethanol is less than 55°.
3. 3. The protective film according to claim 1, wherein the ratio of the gloss value of the protective film surface after immersion in 2-aminoethanol to the gloss value of the protective film surface before immersion in 2-aminoethanol is 40% or more and less than 130%.
4. 4. The protective film-formed film according to claim 1, wherein the Young's modulus of the protective film after immersion in 2-aminoethanol is less than 1000 MPa.
5. 5. The protective film-formed film according to claim 1, wherein the protective film has a breaking elongation of 15% or more after immersion in 2-aminoethanol.
6. A sheet for forming a protective film, comprising: the protective film-forming film according to claim 1 ; and a release film disposed on at least one main surface of the protective film-forming film.
7. A composite sheet for forming a protective film, comprising: the protective film-forming film according to claim 1 ; and a support sheet for supporting the protective film-forming film.
8. A step of attaching the protective film-forming film of the sheet for forming a protective film according to claim 6 or the protective film-forming film of the composite sheet for forming a protective film according to claim 7 to the back surface of a work; A step of converting the attached protective film-forming film into a protective film; A step of dividing the workpiece having a protective film on the back surface or the workpiece having a protective film-forming film on the back surface into individual pieces to obtain a plurality of workpieces having protective films or a plurality of workpieces having protective film-forming films; A step of placing the workpiece with the protective film or the workpiece with the protective film-forming film on a substrate in contact with a flux; A step of heating the workpiece with the protective film arranged on a substrate or the workpiece with the protective film-forming film arranged on a substrate and the substrate; A method for manufacturing an apparatus, comprising the steps of: after the protective film forming step and the heating step, cleaning the substrate on which the workpiece with the protective film is placed with a flux cleaning agent.
9. The method for manufacturing the device according to claim 8 , further comprising a step of performing laser marking on the protective film or the protective film-forming film.
Citation Information
Patent Citations
Method for soldering printed wiring board
JP1996195549A
Pressure-sensitive adhesive sheet for marking
JP2007197668A
Process for preparing film-like adhesive
JP2010018814A
Film for flip-chip type semiconductor rear face, and use thereof
JP2012033626A
Method for manufacturing circuit board with solder solidified, method for manufacturing circuit board with electronic component mounted thereon, and detergent composition for flux
JP2015216276A